Analisis Rasio Efektivitas PAD Terhadap Kinerja Keuangan Daerah Kota Jakarta periode 2015-2019 - Arya Putra Supriyadi; Fandi Ahmad (Universitas Bina Sarana Informatika, 2021)
Abstract - Currently, every organization seeks to maintain performance in order to win the competition, and find out the progress of the organization can be seen by paying attention to financial performance, this study tries to examine and assess the financial performance of the Jakarta City Government for the 2015-2019 budget period by utilizing the results of the review of the Original Income ratio. Regions (PAD), as well as the effectiveness ratio of PAD in the report regarding the realization contained in the Regional Budget (APBD) of the Regional Government of the City of Jakarta. By utilizing a data source in the form of a Budget Realization Report for the 2015-2019 budget period which is based on the Regional Government Financial Report (LKPD) of the Jakarta City Government. This study uses a mixed-method approach technique, namely the researcher tries to analyze financial data to further attempt to describe the existing findings. From the research results, it is known that the calculation of the effectiveness ratio is by dividing the amount of realization of PAD compared to the target PAD set based on the real potential in the region, or in other words, the effectiveness ratio of PAD is obtained by making a comparison between real revenue in PAD to achieve PAD ). From data processing, it is known that the percentage of effectiveness of PAD in the City of Jakarta for the 2015-2019 budget year has reached an average level of achievement of 95.4% of the determined amount or it can be said that it has reached the category of effective criteria.